Bases filosóficas de los análisis cladísticos para la investigación taxonómica - De Luna, Efrain (Instituto de Ecología, A.C., 1995)
This paper reviews three aspects of the relationship between systematics and philosophy, based on an examination of the relevant literature: I) Ontology of natural groups. It is pointed out that phenetic philosophy is associated with an ontological view that natural groups are “classes”, whereas cladistic philosophy is compatible with a concept of taxa as “individuals”. II) Bases for classification. The debate about these bases is whether all similarities by themselves (phenetic approach) or inferred homology based on special similarities (cladistic and traditional approaches) should be used to construct a classification. III) Hypothesis testing. This problem concerns directly the scientific status of each of the three main systematic approaches. The phenetic philosophy that claims being “theory neutral” and the traditional approach without a critical system to test hypothesis are elliminated as “scientific” under popperian criteria. Cladistic philosophy is a robust scientific program because it evolves an explicit and rigorous system for hypothesis refutation at all levels of character and cladistic analysis. In conclusion, it is argued that the selection of an approach to systematics should not be based on operative advantages, but must be a consequence of selecting first an ontological position.